2014
DOI: 10.1177/0891243214523123
|View full text |Cite
|
Sign up to set email alerts
|

Relational Power, Legitimation, and Pregnancy Discrimination

Abstract: Pregnancy-based employment discrimination has long been a topic of interest for gender

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 42 publications
2
40
0
2
Order By: Relevance
“…Even when factoring in human capital, work experience, occupation and industry, and union status, 9% of the wage gap is still unexplained (Blau and Kahn ). This lingering gap is often attributed to implicit bias and subtle discrimination, including discrimination against mothers (Benard and Correll ; Byron and Roscigno ; Correll et al ; Cuddy et al ; Glass ; Kelly and Grant ).…”
Section: The “Stalled Revolution” At Workmentioning
confidence: 99%
“…Even when factoring in human capital, work experience, occupation and industry, and union status, 9% of the wage gap is still unexplained (Blau and Kahn ). This lingering gap is often attributed to implicit bias and subtle discrimination, including discrimination against mothers (Benard and Correll ; Byron and Roscigno ; Correll et al ; Cuddy et al ; Glass ; Kelly and Grant ).…”
Section: The “Stalled Revolution” At Workmentioning
confidence: 99%
“…Correll, Benard, and Paik’s (2007) experimental and audit study showed that mothers received lower competency and commitment ratings, lower suggested salaries, and lower call-back rates for a midlevel marketing position, compared with nonmothers and fathers. 3 Similarly, in ethnographic work, Dodson (2013) found that employers cast low-wage mothers as “irresponsible” when they faced conflicts between work and child care; and in their analysis of pregnancy cases, Byron and Roscigno (2014) reported that employers portrayed complainants as not dependable and incompetent—a practice they called “symbolic vilification”—to justify firing them.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Stereotyping influences perceptions or expectations of pregnant employees’ and working mothers’ abilities, commitment, performance, and appropriateness for authority. Recent research [ 23 ] explored pregnancy-based discrimination, and identified processes of ‘symbolic vilification’ and ‘amplification’ in firing decisions. Pregnant workers were stigmatized through ‘ symbolic vilification’ of their competence and commitment that included charges of poor performance, proneness to absenteeism, unreliability and quitting.…”
Section: Findings: Reasons Behind the Gender Imbalance In Senior Rolementioning
confidence: 99%
“…Regardless of the female employee's actual competence and commitment, pregnancy encouraged managers to amplify the ‘organizational good’ in order to legitimize their biases and justify dismissal or demotion. In this way, discriminatory treatment was passed off as a legitimate process in the service of reaching organizational goals [ 23 ].…”
Section: Findings: Reasons Behind the Gender Imbalance In Senior Rolementioning
confidence: 99%